"Cannabis Businesses Are Being Good Contributors to the Community": The Regulated Cannabis Industry and Cannabis Normalization in the United States - Kinney, Alexander B. (Crime & delinquency, 2025)
This study examines how regulated cannabis businesses normalize their trade in the United States. Using interviews (N?=?56) and a cross-sectional survey of cannabis professionals (N?=?144), I find that the U.S. cannabis industry employs three strategies: (1) Using deviant practices to engage in legitimate business, (2) Reconciling divergent cultural frames for reducing stigma against the cannabis industry, and (3) Changing discursive repertoires that uniquely stigmatize cannabis and cannabis users. I argue that each strategy constitutes a new analytical category of social skill that contested industries leverage in a gray market context.